The Classification Of Maintenance Level Of Gedong Mango With HSI Color Space Transformation Algorithm - Riana; Paska Marto Hasugian (Putaka Timur Publisher, 2021)
The role of technology in its development is very helpful for every type of human work that uses technological assistance. One of the sectors of human work that applies technology in the agricultural sector. In the agricultural sector, one of the commodities in it is the farmer/owner of gedong mango. increase production yield. Mango (Mangifera indicaL) is a fruit originating from India, mango has many varieties. Mangoes are generally marketed in fresh form. This research is useful to increase the bargaining value or value of the owners of mangoes and to create uniformity between owners of mangoes A and owners of mangoes B so that there is no difference in prices given by mango collectors. For example, if the mango is still unripe or too ripe, the selling value will decrease. So it is necessary to classify the maturity range of how many mangoes to get high profits. The intended target is the owner of mango trees in Perumnas Block A Nangka Hamlet, Melati Village II, Kec. Perbaungan Kab. Serdang Bedagai, North Sumatra 20986.